Entre a casa, o mar e a galeria. Os objetos animados de Salette Tavares - Margarida Brito Alves (Midas: Museus e Estudos Interdisciplinares)
Drawing from the articulation between the literary activity and the artistic practice of Salette Tavares (1922-1994), and taking into consideration the multiple connections that her work establishes with everyday life, this article focuses on this artist’s production of objects, in particular, the Creative Dialogues – a set of objects that has not yet been thoroughly studied, developed between 1959 and 1971. These objects take on a playful and everyday dimension, which corresponds to a process of communication between the artist and some of the people who were closest to her. In this sense, the tensions that these objects establish between physical and immaterial, between personal and relational, or between art and life, are analysed, as well as the relationship between the Creative Dialogues and several other works of the artist. Taking as a reference Salette Tavares’ retrospective exhibition, Brincar – organized at the Quadrum Gallery in 1979 –, this article also problematizes the change operated in these objects by moving them from an everyday sphere to an exhibition system.